Preference for daily (1HP) vs. weekly (3HP) isoniazid-rifapentine among people living with HIV in Uganda - A. Musinguzi; H. E. Aschmann; J. L. Kadota; J. Nakimuli; F. Welishe; J. Kakeeto; C. Namale; L. Akello; A. Nakitende; C. Berger; A. Katamba; J. Tumuhamye; et al. (IJTLD Open)
BACKGROUND: Both 1 month of daily (1HP) and 3 months of weekly (3HP) isoniazid-rifapentine are recommended as short-course regimens for TB prevention among people living with HIV (PLHIV). We aimed to assess acceptability and preferences for 1HP vs. 3HP among PLHIV. METHODS: In a cross-sectional survey among PLHIV at an HIV clinic in Kampala, Uganda, participants were randomly assigned to a hypothetical scenario of receiving 1HP or 3HP. Participants rated their level of perceived intention and confidence to complete treatment using a 0–10 Likert scale, and chose between 1HP and 3HP. RESULTS: Among 429 respondents (median age: 43 years, 71% female, median time on ART: 10 years), intention and confidence were rated high for both regimens. Intention to complete treatment was rated at least 7/10 by 92% (189/206 randomized to 1HP) and 93% (207/223 randomized to 3HP). Respectively 86% (178/206) and 93% (208/223) expressed high confidence to complete treatment. Overall, 81% (348/429) preferred 3HP over 1HP. CONCLUSIONS: Both 1HP and 3HP were highly acceptable regimens, with 3HP preferred by most PLHIV. Weekly, rather than daily, dosing appears preferable to shorter duration of treatment, which should inform scale-up and further development of short-course regimens for TB prevention.